Correlation of E-Learning Courses toward Nursing Students’ Cognitive Skills - Fahni Haris; Sri Yusrian (IJNP (Indonesian Journal of Nursing Practices), 2019)
Background: E-learning is one of the new learning methods in the Indonesian education system. This system has been used to increase students’ understanding levels. The researcher has noticed that students had a lack of cognitive level due to the misinterpretation and mis-extrapolation of the materials. E-learning shall improve students’ cognitive level in courses. The researcher is interested in exploring the correlation between the effectiveness of online classes and nursing students’ cognitive level. Objective: This study aims to identify the relationship between the effectiveness of online courses through the e-learning system and students’ understanding level at Universitas Muhammadiyah Yogyakarta. Method: This study implemented a quantitative method with a cross-sectional design along with The Pearson product-moment correlation to measure the correlation strength. Results: The researcher found E-learning adequate to be applied to nursing students of Universitas Muhammadiyah Yogyakarta (85.8% out of total respondents, N=288). The average score of the seven components measured (productivity, quality, efficiency, flexibility, eminence, development, and satisfaction) was 68.54, while the average rating of students’ cognitive level was 53.92.Conclusion: There was a significant correlation between e-learning as an education system and nursing students’ cognitive level.